Development of biodiversity enrichment e-module fauna Gembira Loka Zoo for high school students - Bellamerna Dwi Nawangsih Nurandari; T. Triatmanto (Universitas Muhammadiyah Malang, 2023)
The existence of contextual learning resources that are able to accommodate students' enrichment materials independently is still not found too much. The aims of this study were to: 1) examine the diversity of fauna at Gembira Loka Zoo; and 2) developing an e-module for material enrichment on the topic of biodiversity by utilizing the results of research on faunal diversity at Gembira Loka Zoo. This Research and Development (RnD) used three main stages of the 4D model, namely define, design, and develop. The results showed that at Gembira Loka Zoo there were 88 types of fauna, including Class Gnathostomata, Class Amphibia, Reptiles, Aves, and Mammals, then the conservation agency used SEAZA guidelines for the welfare and care of the fauna. The data is then developed into an e-module for the enrichment of fauna biodiversity which has the potential as a learning resource. The e-modules that have been compiled are considered feasible by material experts, media, and educators to be used on the correctness of the concept as well as aspects of content, appearance, graphics, programming, language, and independent learning. The compiled e-modules can also be read and considered attractive by students in the aspects of content, appearance, programming, language, and independent learning. The modules that have been developed through this research are expected to be used for biology enrichment in various schools in Yogyakarta.